Sex-related differences in oxidative stress and neurodegeneration - Tenkorang, Mavis A. (Steroids, 2017)
Oxidative stress has been implicated in a number of neurodegenerative diseases spanning various fields of research. Reactive oxygen species can be beneficial or harmful, depending on their concentration. High levels of reactive oxygen species can lead to oxidative stress, which is an imbalance between free radicals and antioxidants. Increased oxidative stress can result in cell loss. Interestingly, sex differences have been observed in oxidative stress generation, which may underlie sex differences observed in neurodegenerative disorders. An enhanced knowledge of the role of sex hormones on oxidative stress signaling and cell loss can yield valuable information, leading to sex-based mechanistic approaches to neurodegeneration.